Semiconductor Nanomaterials, Nanotechnology and Nanoelectronic - Фреїк, Дмитро Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
There are the review of science papers, devoted research of classic size effect in lead chalkogenide thin films with a different structural completeness. The influence of inter-phase and inter-grain boundaries, and dislocations of disparity and on the transport phenomena and current carriers mobility within the framework of characteristic lengths, and diffuse scattering, and Petrits model are considered.